Structural Equation Modeling of Intolerance of Uncertainty and Anxiety Sensitivity in Early Adolescence - Nguyen, Thi Lan; Aydemir, Selin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to examine, through structural equation modeling, the direct predictive effect of intolerance of uncertainty on anxiety sensitivity among early adolescents.Methods and Materials: This quantitative cross-sectional study was conducted with a sample of 428 early adolescents aged 11 to 14 years enrolled in public middle schools in Turkey. Participants were selected using multistage cluster sampling from urban districts representing middle socioeconomic status. Data were collected using standardized self-report measures assessing intolerance of uncertainty and anxiety sensitivity, both of which demonstrated satisfactory internal consistency in the present sample. After preliminary screening for missing data, normality, and outliers, confirmatory factor analyses were conducted to validate the measurement models. Structural equation modeling with maximum likelihood estimation was then employed to test the hypothesized direct path from intolerance of uncertainty to anxiety sensitivity. Model fit was evaluated using multiple goodness-of-fit indices, including chi-square to degrees of freedom ratio, Comparative Fit Index, Tucker–Lewis Index, Root Mean Square Error of Approximation, and Standardized Root Mean Square Residual.Findings: The measurement models demonstrated acceptable to good fit indices, confirming the adequacy of the latent constructs. The structural model also showed satisfactory fit to the data. Intolerance of uncertainty significantly and positively predicted anxiety sensitivity (β = .63, p < .001). The model explained 40 percent of the variance in anxiety sensitivity, indicating a substantial effect size. All standardized factor loadings were statistically significant and within acceptable ranges, supporting the reliability of the latent structure.Conclusion: The findings indicate that intolerance of uncertainty functions as a strong cognitive vulnerability factor predicting anxiety sensitivity in early adolescence. These results support transdiagnostic models of anxiety and highlight the importance of targeting intolerance of uncertainty in early preventive and intervention efforts aimed at reducing anxiety-related sensitivity and emotional distress during adolescence.